Neuroacanthocytosis Syndromes: The Clinical Perspective - Walker, Ruth H.; Peikert, Kevin; Jung, Hans H.; Hermann, Andreas; Danek, Adrian (Contact, 2023)
The two very rare neurodegenerative diseases historically known as the “neuroacanthocytosis syndromes” are due to mutations of either VPS13A or XK. These are phenotypically similar disorders that affect primarily the basal ganglia and hence result in involuntary abnormal movements as well as neuropsychiatric and cognitive alterations. There are other shared features such as abnormalities of red cell membranes which result in acanthocytes, whose relationship to neurodegeneration is not yet known. Recent insights into the functions of these two proteins suggest dysfunction of lipid processing and trafficking at the subcellular level and may provide a mechanism for neuronal dysfunction and death, and potentially a target for therapeutic interventions.